Pengaruh Komite Audit, Kepemilikan Keluarga Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2017-2019 - Muhammad Lubara; Damayanti Damayanti; Anita Kusuma Dewi (Jurnal Ilmiah ESAI, 2022)
This study aimed to examine the effect of audit committee, family ownership on tax avoidance by focusing on manufacturing companies Iisted in the lndonesia Stock Exchange in the period 2017-2019. Tax avoidance is a dependent variable, while audit committee, and family ownership is independent variables. The sampling method used was purposive sampling with a sample of 47 companies during the observation period of 3 years in a row to produce a total of 141 samples. The analysis technique used in this research is multiple Iinear regression analysis. Data were analyzed using SPSS 22 version. The results of this study indicate that audit committee does not effect tax avoidance, family ownership has an effect on tax avoidance.